2012
DOI: 10.1248/bpb.b12-00492
|View full text |Cite
|
Sign up to set email alerts
|

Sulfatides Inhibit Adhesion, Migration, and Invasion of Murine Melanoma B16F10 Cell Line <i>in Vitro</i>

Abstract: Endogenous sulfatide, such as 3-sulfated galactosylceramide (3-sulfatide) has been reported to be involved in neuronal development and regulation of tumor cell metastasis. Recently, a new 6-sulfated glucosylceramide (6-sulfatide) has been isolated from the ascidian, Ciona intestinalis. To determine the antitumor function of the new sulfatide, we examined the effects of synthetic 6-sulfatide and 3-sulfatide on the metastatic features of a murine melanoma cell line, B16F10. Both sulfatides significantly inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…One of the known ligands to bind to cancer tissue is sulfatide. Sulfatide plays an important role in several biological systems and binds to a number of proteins, including selectin, which is important for metastasis (Ozawa et al, 2012). Many researchers used sulfatide to target drug carriers in specific cell tissues (Li et al, 2014; Lin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…One of the known ligands to bind to cancer tissue is sulfatide. Sulfatide plays an important role in several biological systems and binds to a number of proteins, including selectin, which is important for metastasis (Ozawa et al, 2012). Many researchers used sulfatide to target drug carriers in specific cell tissues (Li et al, 2014; Lin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the course of our studies on natural oligosaccharides from invertebrate animal species, we are interested in the unique glycosphingolipids (GSLs) and glycoproteins (GPs) found in various Protostomia phyla and we have synthesized these oligosaccharides in order to elucidate biological functions [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In particular, our interests have been focused on the unique oligosaccharide structures of GSLs and GPs found in several parasites including Echinococcus multilocularis [ 2 , 7 , 8 , 11 , 12 , 13 , 15 ], Schistosoma mansoni [ 5 , 10 ], Ascaris suum [ 1 , 17 ], and Toxocara canis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, we have been studying the structure activity relationships of glycosphingolipids from invertebrates animal species and have synthesized oligosaccharides from various Protostomia phyla. [1][2][3][4][5][6][7][8][9][10] Geyer et al identified glycosphingolipids having arthro-series carbohydrate structure (GlcNAcβ1 3Manβ1 4Glcβ1 ) from a parasitic nematode Ascaris suum. 11) In our previous paper, 12) we reported the total synthesis of two glycosphingolipids, GlcNAcβ1 3Manβ1 4Glcβ1 Cer and GalNAcβ 1 4GlcNAcβ1 3Manβ1 4Glcβ1 Cer.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this information we synthesized non-reducing end fragments of novel carbohydrate structures A-E from A. suum previously reported by Geyer and colleagues, 17) i.e. biotin-tagged oligosaccharides (1)(2)(3)(4)(5) (Figs. 1, 2).…”
Section: Introductionmentioning
confidence: 99%